2004
DOI: 10.1073/pnas.0400659101
|View full text |Cite
|
Sign up to set email alerts
|

The plant hormone indoleacetic acid induces invasive growth in Saccharomyces cerevisiae

Abstract: Fungi must recognize plant-specific signals to initiate subsequent morphogenetic events such as filamentation that lead to infection. Here we show that the plant hormone indoleacetic acid (IAA) induces adhesion and filamentation of Saccharomyces cerevisiae. Genome expression profiling of cells treated with IAA identified Yap1, a fungal specific transcription factor, as a key mediator of this response. Strains lacking YAP1 (yap1-1) are hypersensitive to growth on IAA because they accumulate more IAA than can wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(188 citation statements)
references
References 22 publications
7
177
2
2
Order By: Relevance
“…IAA is different from previously described signaling factors because its effects appear to cross species barriers. Prusty et al 13 reported that IAA promoted the growth of filamentous forms of Saccharomyces cerevisiae and promoted the invasion of the yeast, which supports the role of IAA as a signaling molecule regulating yeast growth. In their radioactivity studies of 3 H-IAA, they proved that IAA is taken up by cells and there exists a transport system for IAA uptake.…”
Section: Iaa In Fungal -Fungal Interactionsmentioning
confidence: 90%
See 3 more Smart Citations
“…IAA is different from previously described signaling factors because its effects appear to cross species barriers. Prusty et al 13 reported that IAA promoted the growth of filamentous forms of Saccharomyces cerevisiae and promoted the invasion of the yeast, which supports the role of IAA as a signaling molecule regulating yeast growth. In their radioactivity studies of 3 H-IAA, they proved that IAA is taken up by cells and there exists a transport system for IAA uptake.…”
Section: Iaa In Fungal -Fungal Interactionsmentioning
confidence: 90%
“…Similarly, previous studies have reported that IAA inhibits the growth of plant-associated fungi. 13,25 Kulkarni et al 25 showed that IAA influenced the growth of the plant pathogen F. delphinoides. Exogenous IAA at low concentrations increased the growth of F. delphinoides, whereas at high concentrations, it reduced the growth of F. delphinoides.…”
Section: Iaa In Fungal -Fungal Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the yeast FLO11 gene is induced by auxin, a plant hormone that is produced at plant wound sites [18]. When a population of S. cerevisiae is placed in conditions that induce FLO11 expression, a minority of cells retain an inactive locus.…”
Section: Common Functions Of Gene Silencing In Disparate Life Formsmentioning
confidence: 99%